(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
We conduct empirical analyses on comparing the spillover effects of oil price shocks on the volatility of stock returns between oil importing and oil exporting countries. In particular, we seek to study how the nature of oil price shocks differs due to the oil dependency factor and how the stock markets react to such shocks. Applying the multivariate GARCH-BEKK(1,1) model, our results detect spillover effects between crude oil price and stock returns for all countries. The short run persistencies of shocks are smaller but the persistencies of shocks are very high in the long run. The results hold for both groups of countries. The results imply larger spillover effect from oil price shock into stock market in the oil importing countries.